2007
DOI: 10.4141/cjps06060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium fertilizer source and rate on grain yield and selenium and cadmium concentration of durum wheat

Abstract: Field studies were conducted for 3 yr at two locations in Manitoba, Canada, to evaluate the effect of various sources and rates of Se fertilizer on crop growth and the Se and Cd concentrations of durum wheat. Selenium concentration in durum wheat grown without Se application ranged from 195 to 532 µg kg-1 over the 6 site-years. Selenium seed coating, “Selcote” commercial granular fertilizer, and a foliar spray of sodium selenate solution applied at Feekes stage 5 all increased Se concentration in durum wheat g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 22 publications
4
12
1
Order By: Relevance
“…There were no gains or losses in yield or harvest index upon addition of selenate at application rates of up to 100 g Se ha −1 . These observations are consistent with other studies on field-grown wheat (Curtin et al 2008;Ducsay and Ložek 2006;Grant et al 2007). In controlledenvironment studies, growth stimulations induced by selenate fertilisation have been reported in ryegrass Fig.…”
Section: Discussionsupporting
confidence: 95%
“…There were no gains or losses in yield or harvest index upon addition of selenate at application rates of up to 100 g Se ha −1 . These observations are consistent with other studies on field-grown wheat (Curtin et al 2008;Ducsay and Ložek 2006;Grant et al 2007). In controlledenvironment studies, growth stimulations induced by selenate fertilisation have been reported in ryegrass Fig.…”
Section: Discussionsupporting
confidence: 95%
“…Compared with the control plants, Se translocation was in plants, have been previously reported (Tripathi and Misra, 1974;Lintschinger et al, 2000). The data presented here is in line with previous reports (Grant et al, 2007;Lyons et al, 2005) and confirms findings by Gupta and MacLeod (1999) in soybean. Seed treatment with vit is usually performed to protect crops against soilborne fungal pathogens (Gilbert and Tekauz, 1995), but some ingredients may affect seed germination in some crops.…”
Section: Effect Of Selenium Seed Coating On Harvested Seed Selenium Csupporting
confidence: 93%
“…Spraying Se fertilizer is a new practice for high‐quality production in tree fruit cultivation, and an effective method of developing Se‐enriched fruit . Various studies have revealed that Se fertilizer can improve yield and quality in wheat and rice . Moreover, it can effectively increase Se content of crop edible parts and reduce accumulation of heavy metals .…”
Section: Introductionmentioning
confidence: 99%
“…7 Various studies have revealed that Se fertilizer can improve yield and quality in wheat and rice. 8,9 Moreover, it can effectively increase Se content of crop edible parts 10,11 and reduce accumulation of heavy metals. 12 Most of those studies, however, have selected inorganic Se as the main source of Se fertilizer, and more focused on the effects of application method, 9 application rate and number on crop quality and Se concentration.…”
Section: Introductionmentioning
confidence: 99%